2005
DOI: 10.1021/bi0472954
|View full text |Cite
|
Sign up to set email alerts
|

Unique Substrate Specificity of Anaplastic Lymphoma Kinase (ALK):  Development of Phosphoacceptor Peptides for the Assay of ALK Activity

Abstract: The anaplastic lymphoma kinase (ALK), whose constitutively active fusion proteins are responsible for 5-10% of non-Hodgkin's lymphomas, shares with the other members of the insulin receptor kinase (IRK) subfamily an activation loop (A-loop) with the triple tyrosine motif Y-x-x-x-Y-Y. However, the amino acid sequence of the ALK A-loop differs significantly from the sequences of both the IRK A-loop and the consensus A-loop for this kinase subfamily. A major difference is the presence of a unique "RAS" triplet be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
65
2

Year Published

2007
2007
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(70 citation statements)
references
References 38 publications
3
65
2
Order By: Relevance
“…Interactions of the A-loop ␣-helix with both the N-terminal and C-terminal lobes of the kinase and a hydrogen bond between Tyr 1278 and Cys 1097 from the N-terminal ␤-turn motif serve to stabilize the observed conformation. The fact that Tyr 1278 is phosphorylated upon formation of fully activated ALK underscores the inactive nature of the observed structures (40,41). The fully activated ALK kinase is expected to resemble the activated form of the insulin receptor kinase (IRK), the structure of which has been reported previously using the Tris-phosphorylated IRK kinase domain crystallized with a substrate peptide and an ATP analog (42).…”
Section: Anaplastic Lymphoma Kinase (Alk)mentioning
confidence: 67%
See 1 more Smart Citation
“…Interactions of the A-loop ␣-helix with both the N-terminal and C-terminal lobes of the kinase and a hydrogen bond between Tyr 1278 and Cys 1097 from the N-terminal ␤-turn motif serve to stabilize the observed conformation. The fact that Tyr 1278 is phosphorylated upon formation of fully activated ALK underscores the inactive nature of the observed structures (40,41). The fully activated ALK kinase is expected to resemble the activated form of the insulin receptor kinase (IRK), the structure of which has been reported previously using the Tris-phosphorylated IRK kinase domain crystallized with a substrate peptide and an ATP analog (42).…”
Section: Anaplastic Lymphoma Kinase (Alk)mentioning
confidence: 67%
“…The fact that Tyr 1278 makes no specific hydrogen bonding interactions in this structure and is adjacent to the beginning of the disordered region of the A-loop is clearly suggestive of more facile autophosphorylation of this residue. As previous studies have shown that Tyr 1278 , the first residue in the activation loop YXXXYY motif, is a key driver of ALK activation, the R1275Q structure provides a structural rationale of the activating nature of this mutant (40,41).…”
Section: Crystallization Of the Alk Kinase Domain By In Situmentioning
confidence: 99%
“…4A). The same immunoprecipitates were subjected to an in vitro kinase assay with the synthetic peptide YFF (12). Each variant protein (with the exception of the kinase-inactive mutant of variant 1) was shown to possess protein tyrosine kinase activity, with that of variants 3a, 3b, and 5b being most prominent (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The resulting plasmids and similar pMXS-based expression plasmids for EML4-ALK variant 1, variant 1(K589M), variant 2, variant 3a, and variant 3b were individually introduced into HEK293 cells. Lysates of the transfected cells were subjected to immunoprecipitation with antibodies to FLAG, and the resulting precipitates were subjected either to immunoblot analysis with the same antibodies or to an in vitro kinase assay with the YFF peptide (12). Mouse 3T3 fibroblasts were also infected with recombinant retroviruses for each of the EML4-ALK variants or wild-type ALK and were then cultured for 12 d for a focus formation assay.…”
Section: Translational Relevancementioning
confidence: 99%
“…[21][22][23] The nonreceptor tyrosine kinases Lyn, c-Fgr, Syk and Csk were purified from rat spleen to near homogeneity 22 (details are given in the Online Supplementary Appendix).…”
Section: Preparation Of Recombinant and Native Protein Kinasesmentioning
confidence: 99%